Chemical constituents from the root bark of Cynanchum auriculatum. (December 2018) - Wang, Xin-Jie; Lv, Xu-Hui; Li, Zhen-Lin; Qian, Shi-Hui; Pu, She-Ban
Abstract: Sixteen compounds, including five triterpenoids (1–5 ), five C21 -steroids (6–10 ), two other steroids (11–12 ), two phenols (13–14 ) and others (15–16 ), were isolated from the root bark of Cynanchum auriculatum Royle ex Wight. Their chemical structures were determined by spectral data analyses. In the present research, compound11 is reported for the first time in the species C. auriculatum . Compounds2 ∼5, 12, 15 and16 have not been reported from any species in Asclepiadaceae family. Moreover, the chemotaxonomic significance of the isolated compounds is discussed. Highlights: Sixteen compounds isolated from C. auriculatum were assigned as triterpenoids, C21 -steroids, steroids, substituted benzenes and others. Compound11 has not been reported in the species of C. auriculatum and compounds2 –5, 12, 15, 16 were new for the family of Asclepiadaceae. Compounds1, 8, 11 may be useful chemotaxonomic markers to differentiate C. auriculatum from other species of Cynanchum . Further work needs to be done on the distribution of these compounds in the genus of Cynanchum to evaluate whether they have systematic value.